2D/3D coordination polymers: treatment effect on the ulcerative colitis by reducing the inflammatory response. Issue 5 (18th August 2020) - Ma, Li-Qun; Han, Qiang; Mei, Chen
Abstract: Two new mixed-ligand coordination polymers with the chemical formulae of [Co(L1 )(bdc)](H2 O)n (1, L1 = 1, 4-bis((1H-benzo[d]imidazol-1-yl)methyl)benzene, H2 bdc = terephthalic acid) and [Co(L2 )(bdc)](H2 O)n (2, L2 = 1, 3-bis((1H-benzo[d]imidazol-1-yl)methyl)benzene) have been successfully prepared by the solvothermal treatment of H2 bdc and different N-donor co-ligands with Co(II) salt. In biological functional study, the treatment effect of compounds 1 and 2 on the ulcerative colitis (UC) was evaluated. Firstly, the ELISA assay was performed to reveal the changes of the inflammatory cytokines caused by compounds. Besides, the model of mice was established and the mice' body weight was measured and recorded at the 7th and 14th day after compounds treatment.